A triple-masked, two-center, randomized parallel clinical trial to assess the superiority of eight weeks of grape seed flour supplementation against placebo for weight loss attenuation during perioperative period in patients with cachexia associated with colorectal cancer: a study protocol - Malta, Felipe Aguiar Pupo Seabra; Gonçalves, Daniela Caetano (Frontiers in Endocrinology, 2024)
Background Progressive, involuntary weight and lean mass loss in cancer are linked to cachexia, a prevalent syndrome in gastrointestinal malignancies that impacts quality of life, survival and postoperative complications. Its pathophysiology is complex and believed to involve proinflammatory cytokine-mediated systemic inflammation resulting from tumor-host interaction, oxidative stress, abnormal metabolism and neuroendocrine changes. Therapeutic options for cachexia remain extremely limited, highlighting the need for clinical research targeting new interventions. Thus, this study primarily assesses the effects of grape-seed flour (GSF), rich in polyphenols and fibers, for attenuating perioperative weight loss in colorectal cancer. Methods This is a dual-center, triple-masked, placebo-controlled, parallel-group, phase II, randomized clinical trial designed to investigate GSF supplementation in subjects with pre- or cachexia associated with colorectal cancer during the perioperative period. Eighty-two participants will receive 8g of GSF or cornstarch (control) for 8 weeks. Assessments are scheduled around surgery: pre-intervention (4 weeks prior), day before, first week after, and post-intervention (4 weeks later). The primary endpoint is the difference in body weight mean change from baseline to week 8. The secondary endpoints describe the harms from 8-week supplementation and assess its superiority to improve body composition, post-surgical complications, quality of life, anorexia, fatigue, gastrointestinal symptoms, and handgrip strength. The study will also explore its effects on gut bacteria activity and composition, systemic inflammation, and muscle metabolism. Discussion The current trial addresses a gap within the field of cancer cachexia, specifically focusing on the potential role of a nutritional intervention during the acute treatment phase. GSF is expected to modulate inflammation and oxidative stress, both involved in muscle and intestinal dysfunction. The research findings hold substantial implications for enhancing the understanding about cachexia pathophysiology and may offer a new clinical approach to managing cachexia at a critical point in treatment, directly impacting clinical outcomes. Trial registration The Brazilian Registry of Clinical Trials (ReBEC), RBR-5p6nv8b; UTN: U1111-1285-9594. Prospectively registered on February 07, 2023.